THE EFFECT OF “BUFAS SMART” EDUCATION ON THE INCIDENCE OF POSTPARTUM BLUES AT RSUD KARTINI KARANGANYAR - Tri Wikuncoro Tunggal Saputri; Luluk Fajria Maulida; Rufidah Maulina; Siti Nurhidayati; Ika Sumiyarsi Sukamto (Indonesian Midwifery and Health Sciences Journal, 2025)
AbstractBackground: Postpartum blues, maternity blues or baby blues is a temporary mild mood/affect disorder that occurs on the first day to the 10th day after delivery. Postpartum blues usually occurs on the third or fourth postpartum day and peaks between the fifth postpartum day which is characterized by frequent crying, feelings of loneliness or rejection, anxiety, confusion, anxiety, fatigue, forgetfulness and sleeplessness. One of the preventive efforts through health promotion, one of the effective ways is by using social networks. BUFAS SMART is the name of the whatsapp group used to provide education to postpartum mothers conducted for 3 consecutive days on postpartum mothers on day 3 to day 5 in the intervention group with material containing how to care for babies, how to breastfeed, and psychological changes in postpartum women. Method: The sample of this study amounted to 50 respondents of postpartum mothers with purposive sampling technique. This research design uses quasy experiment. This research instrument uses a questionnaire. Data analysis used is Wilcoxon test and Mann-Whitney test. Result: The effect of “BUFAS SMART” education on the incidence of postpartum blues at Kartini Karanganyar Hospital on respondents in the intervention posttest group and control posttest group was significant with the results of the p-value <0.05, which is 0.000, meaning that there is a significant difference between the pretest and posttests of the control group. Conclusion: BUFAS SMART reduces the incidence of postpartum blues at Kartini Karanganyar Hospital, so the BUFAS SMAST education method is suitable for application in postpartum blues mothers add more in-depth knowledge about the postpartum period.